The galenic venous system: Surgical anatomy and its angiographic and magnetic resonance venographic correlations - (:unkn) unknown (ELSEVIER IRELAND LTD, 2005)
Objective: This study aims at evaluating the adequacy of digital subtraction angiography and magnetic resonance venography in imaging of the galenic venous system for surgical planning of approaches to the pineal region. Anatomical dissections were carried out in 10 cadavers of several age groups and these were compared to imaging findings in 10 living subjects. Methods: The presence or absence of 10 predetermined veins or vein groupings belonging to the galenic venous system were prospectively analyzed in 10 cadaver dissections and imaging findings of 10 age matched human subjects. The studied vessels were the vein of galen, the internal cerebral veins, both basal vein of Rosenthals, internal occipital vein, occipitotemporal veins, precentral cerebellar veins, tectal veins, pineal veins, superior vermian veins (including superior cerebellar veins (SCVs)) and posterior pericallosal veins. Each of the subjects had both digital subtraction angiography and magnetic resonance venography studies performed. Diagnostic digital subtraction angiography was performed using the transfemoral route and the venous phase was used for the study. Magnetic resonance venography was performed in 1.5 T MRI equipment using the 2D-TOF sequence. All studies were reported to be normal. Results: There was wide variation in the anatomy of the galenic venous system. There were interpersonal, intrapersonal and age related variations. Both the digital subtraction angiography and the magnetic resonance venography were efficient at demonstrating large veins. However, smaller veins were less readily demonstrated in either study. The general sensitivities of the digital subtraction angiography and the magnetic resonance venography for the galenic venous system were 45.5% and 32.5%, respectively. Surgically important veins were missed in most studies. Conclusions: Anatomically, the galenic venous system is highly variable. This variability is caused by interpersonal, intrapersonal and age related differences and causes each individual galenic venous system to be unique. Therefore, modem neurosurgical procedures require anatomical information on individual differences. Current radiological methods of digital subtraction angiography and magnetic resonance venography fail short of providing the necessary information. New and more sophisticated MRI technology may fulfill this need. (C) 2005 Elsevier Ireland Ltd. All rights reserved.
Keywords: cerebral veins; angiography; magnetic resonance angiography; newborn; adults; cadaver; GREAT CEREBRAL VEIN; MICROSURGICAL ANATOMY; MR-VENOGRAPHY; PINEAL REGION; MICRO-SURGERY; BRAIN; 3RD-VENTRICLE; CONTRAST; INFRATENTORIAL; DRAINAGE